Mapping Process of Digital Forensic Investigation Framework - Selamat, S. R.; Yusof, R.; Sahib, S. (Dr. Sang H. Lee, 2008)
Digital forensics is essential for the successful prosecution of digital criminals which involve diverse digital devices such as computer system devices, network devices, mobile devices and storage devices. The digital forensic investigation must be retrieved to obtain the evidence that will be accepted in the court of law. Therefore, for digital forensic investigation to be performed successfully, there are a number of important steps that have to be taken into consideration. The aim of this paper is to produce the mapping process between the processes/activities and output for each phase in Digital Forensic Investigation Framework (DFIF). Existing digital forensic frameworks will be reviewed and then the mapping is constructed. The result from the mapping process will provide a new framework to optimize the whole investigation process.